(untitled) (Journal of Science and Technology, 2015)
This paper finds the reliability of the average of examination marks, calculated to two decimal places, as a criterion for the ranking and classification of students. The marks are in percentages, and the paper examines the importance of a difference of one point in the unit, the first or the second decimal place. It is seen from the reliability in marking, even the mathematical courses, that the probability of obtaining a re-liable percentage average calculated to one or two decimal places is very low . Thus it is only fair to limit the average marks calculated only up to the units.